GEOMEMÓRIAS: EX SITU GEOCONSERVATION INITIATIVE PROMOTED BY THE DEPARTMENT OF GEOSCIENCES AT THE UNIVERSIDADE FEDERAL DE SANTA MARIA IN CELEBRATION OF THE 60TH ANNIVERSARY OF THE GEOGRAPHY PROGRAMS - Nobre, Augusto Gonçalves; Nummer, Andrea Valli; Sccoti, Anderson Augusto Volpato; Martins, Lucas Storgatto; Pinto, Juliane Dos Santos; Dri, Priscila Picolli; Ceccato, Haline Dugolin; Leal, Andressa Gomes; Lopes, Alyssia Moraes (Boletim Paranaense de Geociências, 2025)
The year 2025 is significant for the Department of Geosciences at the Universidade Federal de Santa Maria, as it marks the 60th anniversary of the establishment of the university’s first Geography program. As a way to contribute to the scheduled celebrations and to leave a long-term legacy, the interactive space Geomemórias is being developed. This space will feature activities and exhibitions of geological materials from the four main geomorphological provinces of the state of Rio Grande do Sul, promoting the integration of geology with physical geography, while also encouraging ex situ geoconservation initiatives in other analogous institutions.